Risk of recurrent stroke in Rotterdam between 1990 and 2020: a population-based cohort studyResearch in context - Bernhard P. Berghout; Daniel Bos; Peter J. Koudstaal; M. Arfan Ikram; M. Kamran Ikram (The Lancet Regional Health. Europe, 2023)
Summary: Background: After an initial stroke, current clinical practice is aimed at preventing recurrent stroke. Thus far, population-based estimates on the risk of recurrent stroke remain scarce. Here we describe the risk of recurrent stroke in a population-based cohort study. Methods: We included Rotterdam Study participants who developed a first-ever incident stroke during follow-up between 1990 until 2020. During further follow-up, these participants were monitored for the occurrence of a recurrent stroke. We determined stroke subtypes based on clinical and imaging information. We calculated ten-year overall and sex-specific cumulative incidences of first recurrent stroke. To reflect changing secondary preventive strategies employed in recent decades, we then calculated the risk of recurrent stroke within ten-year epochs based on first-ever stroke date (1990–2000, 2000–2010 and 2010–2020). Findings: In total, 1701 participants (mean age 80.3 years, 59.8% women) from 14,163 community-living individuals suffered a first stroke between 1990 and 2020. Of these strokes, 1111 (65.3%) were ischaemic, 141 (8.3%) haemorrhagic, and 449 (26.4%) unspecified. During 6585.3 person-years of follow-up, 331 (19.5%) suffered a recurrent stroke, of which 178 (53.8%) were ischaemic, 34 (10.3%) haemorrhagic and 119 (36.0%) unspecified. Median time between first and recurrent stroke was 1.8 (interquartile range 0.5–4.6) years. Overall ten-year recurrence risk following first-ever stroke was 18.0% (95% CI 16.2%–19.8%), 19.3% (16.3%–22.3%) in men and 17.1% (14.8%–19.4%) in women. Recurrent stroke risk declined over time, with a ten-year risk of 21.4% (17.9%–24.9%) between 1990 and 2000 and 11.0% (8.3%–13.8%) between 2010 and 2020. Interpretation: In this population-based study, almost one in five people with first-ever stroke suffered a recurrence within ten years of the initial stroke. Furthermore, recurrence risk declined between 2010 and 2020. Funding: Netherlands Organization for Health Research and Development, EU’s Horizon 2020 research programme and the Erasmus Medical Centre MRACE grant.